2023
DOI: 10.1111/os.13678
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Dose, Efficacy and Safety of Tranexamic Acid and Epsilon‐Aminocaproic Acid to Reduce Bleeding in TKA: A Systematic Review and Bayesian Network Meta‐analysis

Abstract: Objective: The optimal dose and efficacy of tranexamic acid (TXA) and epsilon-aminocaproic acid (EACA) in total knee arthroplasty (TKA) were under controversial, and we aimed to make comparisons between different doses of TXA and EACA in intravenous (IV) or intra-articular (IA) applications in patients undergoing TKA.Methods: This network meta-analysis was guided by the Priority Reporting Initiative for Systematic Assessment and Meta-Analysis (PRISMA). According to the administrations of antifibrinolytic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
1
0
2
Order By: Relevance
“…TXA functions as a competitive antagonist of lysine binding sites on plasminogen, plasmin, and tissue plasminogen. This reversible blockade hinders fibrinolysis and degradation of blood clots and is activated intraoperatively and immediately after surgery, thereby reducing bleeding ( 32 , 33 ). A study of 7,331 trauma patients by Knowlton et al ( 34 ), a study of 168 knee arthroplasty procedures by Xue et al ( 35 ), and a posterior spinal surgery study by Luan et al ( 10 ) showed that use of TXA did not increase the risk of venous thrombosis in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…TXA functions as a competitive antagonist of lysine binding sites on plasminogen, plasmin, and tissue plasminogen. This reversible blockade hinders fibrinolysis and degradation of blood clots and is activated intraoperatively and immediately after surgery, thereby reducing bleeding ( 32 , 33 ). A study of 7,331 trauma patients by Knowlton et al ( 34 ), a study of 168 knee arthroplasty procedures by Xue et al ( 35 ), and a posterior spinal surgery study by Luan et al ( 10 ) showed that use of TXA did not increase the risk of venous thrombosis in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…16 Como resultado, lleva a la estabilización de la red de fibrina preformada por la hemostasia secundaria. 19 Previene la descomposición del fibrinógeno, lo que conlleva a una disminución significativa del sangrado. 17 El ATX se concentra de manera efectiva en el tejido articular; su biodisponibilidad es de aproximadamente 30%, siendo su mecanismo de eliminación principalmente por vía renal.…”
Section: Mecanismos De Acciónunclassified
“…La utilización del ATX en la ortopedia se ha enfocado principalmente en el ámbito de la artroplastia total de cadera o rodilla, procedimientos que a menudo conllevan un riesgo significativo de sangrado y complicaciones relacionadas. 19,26,27 Pacientes que experimentan pérdida aguda de sangre debido a sangrado intraoperatorio o postoperatorio importante pueden necesitar recibir transfusiones de productos sanguíneos, lo cual aumenta el riesgo de complicaciones y resulta costoso. 21 Además, las transfusiones de sangre de donantes conllevan riesgos adicionales, como reacciones hemolíticas o anafilácticas, transmisión de infecciones y estancia prolongada en el hospital.…”
Section: Uso En La Artroplastia Total De Rodillaunclassified